2020
DOI: 10.1101/2020.12.29.424482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for broad coronavirus neutralization

Abstract: Three highly pathogenic β-coronaviruses crossed the animal-to-human species barrier in the past two decades: SARS-CoV, MERS-CoV and SARS-CoV-2. SARS-CoV-2 has infected more than 64 million people worldwide, claimed over 1.4 million lives and is responsible for the ongoing COVID-19 pandemic. We isolated a monoclonal antibody, termed B6, cross-reacting with eight β-coronavirus spike glycoproteins, including all five human-infecting β-coronaviruses, and broadly inhibiting entry of pseudotyped viruses from two cor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(123 citation statements)
references
References 151 publications
6
117
0
Order By: Relevance
“…However, the ACE2-binding region of the RBD also tends to accumulate amino acid changes, as evidenced by substitutions identified in the current SARS-CoV-2 variants of concern (Annavajhala et al, 2021;Faria et al, 2021;Rambaut et al, 2020;Tegally et al, 2020;Voloch et al, 2020;West et al, 2021;Zhang et al, 2021), thus reducing the potential efficacies of vaccines and monoclonal antibody therapies. Recent studies suggest that antibodies against the S2 subunit offer the potential of greater cross-reactivity across coronaviruses, but these antibodies generally lack strong neutralization potency (Sauer et al, 2021;Shah et al, 2021;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ACE2-binding region of the RBD also tends to accumulate amino acid changes, as evidenced by substitutions identified in the current SARS-CoV-2 variants of concern (Annavajhala et al, 2021;Faria et al, 2021;Rambaut et al, 2020;Tegally et al, 2020;Voloch et al, 2020;West et al, 2021;Zhang et al, 2021), thus reducing the potential efficacies of vaccines and monoclonal antibody therapies. Recent studies suggest that antibodies against the S2 subunit offer the potential of greater cross-reactivity across coronaviruses, but these antibodies generally lack strong neutralization potency (Sauer et al, 2021;Shah et al, 2021;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…D614G SARS-CoV-2 S (YP 009724390.1), RaTG13 S (QHR63300.2), Pangolin-Guangdong S (QLR06867.1), SARS-CoV S (YP 009825051.1), WIV1 S (AGZ48831.1), B.1.351 S and B1.1.7 S pseudotypes VSV viruses were prepared as described previously 54,86 . Briefly, 293T cells in DMEM supplemented with 10% FBS, 1% PenStrep seeded in 10-cm dishes were transfected with the plasmid encoding for the corresponding S glycoprotein using lipofectamine 2000 (Life Technologies) following manufacturer’s indications.…”
Section: Methods Detailsmentioning
confidence: 99%
“…When it comes to MERS-CoV-specific NmAbs with cross-neutralizing activity against SARS-CoV-2, aside from Chouchane et al ( Chouchane et al, 2021 ) who recently identified MERS-CoV-specific pAbs from non-immunized camel, with SARS-CoV-2 cross neutralization, but without further characterization, only one SARS- and MERS-CoV specific antibody, namely B6 was able to cross-neutralize SARS-CoV-2 in nanomolar concentration range ( Sauer et al, 2021 ).…”
Section: Sars-cov-2 Nmab Molecular Neutralizing Activitiesmentioning
confidence: 99%